PENGEMBANGAN MEDIA ULTAMA (ULAR TANGGA MATEMATIKA) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN MATEMATIKA KELAS 4 SEKOLAH DASAR - Yudistira; Bramianto Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Development of ULTAMA media (math snakes and ladders) to improve students' critical thinking skills in grade 4 elementary school mathematics learning. Supervised by (Bramianto Setiawan, S.Pd., M.Si). This research aims to develop ULTAMA media in mathematics learning to improve students' critical thinking skills. This research was carried out at SDIT AL – Irsyaduddin. This research uses the R&D research method and uses the ADDIE development model which consists of five stages, namely analysis, planning, development, implementation, evaluation. The results of this research and the development of ULTAMA media are (1) the development of ULTAMA media is valid and suitable for testing with a score from media experts is 76%, a score from material experts is 92%, a score from language experts is 86%. The average student response score is 92.6%, and the teacher response score is 93.3%. This score is included in the very practical category, (2) at the understanding and effectiveness stage based on the results of the pre-test and post-test, there are significant differences in learning. before and when using ULTAMA media, the results before (pretest) were 69.21% and the results after using ULTAMA media (posttest) were 91.9% in the very effective category. So it can be concluded that the ULTAMA media developed can be said to be quite effective in improving students' critical thinking skills in mathematics learning.